Self-Dealing : Sneaking Corporate Value through the Back Door - Nenova, Tatiana; Hickey, Catherine (World Bank, Washington, DC, 2012)
Self-dealing, prevalent in emerging markets, often harms minority shareholders. The related-party transaction is one common technique, especially in markets with weak law enforcement. Beyond self-dealing, other methods of expropriation, such as insider trading and dilution of share value, can also harm minorities. Countries can use several tactics to combat self-dealing, including improving disclosure, strengthening regulatory enforcement, and increasing public awareness of good governance and investor rights. While not always successful, these measures often go a long way toward protecting minority investors.